Reorganisation of a legal entity: the essence and understanding of its manifestation (creation or termination) (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The problematic issues related to the legislator’s priority task of regulating changes in the property status of a legal entity in the course of its reorganisation are outlined, which ensures the organisational and legal transformation of the organisation through effective redistribution of resources and enhancing the modernisation of the country’s economic stability as a whole.The current state of the legal doctrine of understanding reorganisation as a legal phenomenon has no common denominator. It is studied as a method of termination of a legal entity; a method of emergence and/or termination of a legal entity(ies); a special procedure for the transfer of rights and obligations; a type of universal succession; a legal remedy; the procedural aspect of reorganisation actions is studied, pointing to the process, composition or set of legal facts, or it is proposed to abandon attempts to define the category of “reorganisation” altogether.Based on the analysis of the legal doctrine and current legislation, the conclusion that reorganisation is a special mechanism of transformation of a legal entity, which is manifested in a complex legal structure aimed at achieving a positive economic effect or bringing it into compliance with current legislation, resulting in termination and/or establishment of a new legal entity(ies) with the transfer to it of the property (or part thereof) of the legal entity being reorganised by way of legal succession, has been made. The opinion that an unambiguous statement that reorganisation is a form of either creation or termination of a legal entity is erroneous has been presented. This conclusion is based on the fact that current legislation enshrines different denominators for certain types of reorganisation – termination/establishment, but the relevant legal phenomenon should be studied comprehensively (as a whole). In this case, one section of such a legal structure will indicate the creation and the other one will indicate the termination of a legal entity, which is manifested within the reorganisation procedure of one organisation.